PENERAPAN MODEL PBL UNTUK MENINGKATKAN KETERAMPILAN MENULIS PERMULAAN MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS 1 SDN GADINGMANGU I - Muarifa, Sulistia; Aspariyah; Fitria Lutfiana, Rose (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Observations in class I at SDN Gadingmangu I found obstacles related to initial writing skills. It can be seen that most of the students in class I have low writing ability. Of the 46 students, 17 students had good writing skills. About 24 children are said to take a long time to write and they still have misspelled and wrong letters. 5 students whose writing is difficult to read. The use of the PBL learning model can help learning become more effective. The material that will be conveyed to students becomes easier to convey. The PBL learning model can make students think more critically with the problems given by the teacher. This classroom action research was carried out using data from observations, interviews, and performance tests. The average value of students' initial writing skills before the action or pre-cycle is 68.78. The results of the assessment in cycle I showed that out of 46 students, 19 students had fulfilled the criteria for successful action. Meanwhile, 27 of them have not reached the criteria for successful action. The average value of beginning writing abilities increased by 71.41 points during the first cycle. The percentage of individuals who met the success criterion was 36.95% in the pre-cycle and 38.150% in the first cycle, a rise of 4.35 percentage points. The results of the assessment in cycle II showed that out of 46 students, 41 students had met the criteria for successful action and as many as 5 students had not met the criteria for successful action. The average value of initial writing skills in cycle I was 71.41 with a percentage of achieving a success criterion of 41.30%, an increase of 47.83% in cycle II.